Football training improves lean body mass in men with prostate cancer undergoing androgen deprivation therapy. (August 2014) - Uth, J.; Hornstrup, T.; Schmidt, J. F.; Christensen, J. F.; Frandsen, C.; Christensen, K. B.; Helge, E. W.; Brasso, K.; Rørth, M.; Midtgaard, J.; Krustrup, P.
Abstract : Androgen deprivation therapy (ADT) remains a cornerstone in the management of patients with prostate cancer (PCa) despite adverse effects on body composition and functional parameters. We compared the effects of football training with standard care in PCa patients managed with ADT (> 6 months). Fifty‐seven men aged 67 (range: 43–74) were randomly assigned to a football group (FG, n  = 29) or a usual care control group (CON, n  = 28). The primary outcome was change in lean body mass (LBM) assessed by dual‐energy X‐ray absorptiometry scanning. Secondary outcomes included changes in knee‐extensor muscle strength (one repetition maximum), fat percentage, and maximal oxygen uptake (VO2max ). Mean heart rate during training was 137.7 (standard deviation 13.7) bpm or 84.6 (3.9)% HRmax. In FG, LBM increased by 0.5 kg [95% confidence interval (CI) 0.1–0.9; P  = 0.02] with no change in CON (mean group difference 0.7 kg; 95% CI 0.1–1.2; P  = 0.02). Also, muscle strength increased in FG (8.9 kg; 95% CI 6.0–11.8; P  < 0.001) with no change in CON (mean group difference 6.7 kg; 95% CI 2.8–10.7; P  < 0.001). In FG, VO2max increased (1.0 mL/kg/min; 95% CI 0.2–1.9; P  = 0.02) and fat percentage tended to decrease (0.7%; 95%CI 1.3–0.0; P  = 0.06), but these changes were not significantly different from CON. In conclusion, football training over 12 weeks improved LBM and muscle strength compared with usual care in men with prostate cancer receiving ADT.